Exploring differences between groove and catchiness - Bechtold, Toni A.; Curry, Ben; Witek, Maria A. G. (Frontiers in Psychology, 2025)
IntroductionGroove and catchiness play a significant role in popular music, and a series of studies has shown that they are positively related. In this study, we explored the limits of this relationship: when are groove and catchiness not related, and which musical factors promote one but not the other? To address the first question, we focused on duration: groove (an urge to move along to music) is thought to require representation of meter and repetition, and thus a certain duration, while catchiness is thought to act within fractions of a second.MethodsIn a listening experiment, 92 participants rated 54 AI-generated music excerpts that varied in style, tempo, and duration (1 second and 10 seconds) on urge to move, pleasure, and catchiness. Additionally, they assigned the stimuli to one or more of 13 popular music styles and completed a recognition task. To examine the influence of musical characteristics, we measured 18 audio features of the music. We analyzed these data using t-tests, correlation analyses, and Bayesian regression models to assess the relationships between listener responses, stimulus conditions, and musical features.Results and discussionEven the 1-second excerpts elicited some urge to move—though less than for 10-second excerpts, while catchiness ratings were on average similar across durations. Catchiness and urge to move ratings were correlated even in the 1-second condition. These findings suggest a complex, reciprocal relationship between catchiness and the urge to move in listeners, which we partly explain through a distinction between ‘transient’ and ‘sustained’ catchiness. We identified some music-related factors that affected only one of the two ratings: rhythmic information and tempo affected urge to move only. In contrast, recognizability substantially increased catchiness but had little effect on the urge to move. Four out of 13 popular music styles (as perceived by participants) affected catchiness but not the urge to move, while three out of 18 audio features affected one but not the other. In summary, while we found further support for a positive relationship between groove and catchiness, this relationship is constrained by duration and certain musical characteristics, which can affect the two responses to music differently.